Analysis of the Application WWHAM Method in Self-Medication Services to Patient Satisfaction at the Healthy Star Pharmacy in Blitar District - Rohim, Abdul; Hanie Kusuma Wardani; Chinthia Devientasari; Hanik Maria Dewi (Strada Journal of Pharmacy, 2025)
Self-medication is the practice of self-medication without a doctor's prescription to treat minor complaints without a doctor's prescription. This study aims to analyse the effect of applying the WWHAM (Who, What, How Long, Action, Medication) method on patient satisfaction in self-medication services at Bintang Sehat Pharmacy in Blitar Regency. The research method used a quantitative approach with a cross-sectional design, this study involved 360 respondents. Data were collected through observations and questionnaires based on the SERVQUAL dimension, and analysed using the Spearman Rank correlation test. The results showed a significant relationship between the implementation of WWHAM and patient satisfaction (r: 0.272, p: 0.000). Tangible, responsiveness, and assurance dimensions obtained the highest level of satisfaction. The conclusion of the study is that there is a correlation between quality and satisfaction. This shows that the more complete and precise the application of the WWHAM method by pharmacists, the level of patient satisfaction with self-medication services will also increase.